Palladium-catalyzed Suzuki-Miyaura coupling of thioureas or thioamides - Shaoyu Mai (Nature Portfolio, 2019)
Alternative carbene precursors for metal-catalyzed cross coupling may expand the portfolio of methods for C-C bond construction. Here, the authors report a Suzuki−Miyaura coupling of Pd−carbene complexes formed by desulfurization of thioureas or thioamides and affording a broad array of amidinium salts and diaryl ketones.